Artificial intelligence as a potential subject of property and intellectual property relations - Некіт, Катерина Георгіївна; Некит, Екатерина Георгиевна; Nekit, Ekaterina G.; Некіт, К. Г.; Nekit, Kateryna H.; Токарева, Віра Олександрівна; Токарева, В. О.; Токарева, Вера Александровна; Tokareva, Vira O.; Зубар, Володимир Михайлович; Зубар, В. М.; Зубар, Владимир Михайлович; et al. (Universidad de Los Hemisferios, 2020)
The article analyzes the possibility to provide legal capacity to artificial intelligence, which would lead to the emergence of a new subject in legal relations. The aim of the article is to reveal whether it is possible to recognize, that artificial intelligence is able to have property and intellectual property rights. To achieve this aim, dialectical, comparative, dogmatic and legal methods are used. It is noted that according to recent studies, there are more and more grounds for recognizing artificial intelligence as subjects of legal relations. Particular attention in the article is paid to the specifics of the status of artificial intelligence in property relations. The consequences of empowering artificial intelligence with the right to property are analyzed. The conclusion is drawn on the appropriateness of such an approach, since this will solve the problem of liability for damage caused by artificial intelligence. The possibility of endowing artificial intelligence with property on the basis of trust before resolving the issue of its legal personality is proposed. Modern approaches to the problem of rights to objects of creativity created by artificial intelligence are considered in the article. The options for the distribution of rights to such objects are analyzed depending on the degree of human participation in their creation and on the level of complexity of the artificial intelligence that creates these objects. The general conclusion is made about the possibility to qualify artificial intelligence as a subject of legal relations, in particular, of property and intellectual property relations.

У статті проаналізовано можливість надання правоздатності штучному інтелекту, що призвело б до появи нового суб’єкта у правовідносинах. Мета статті - виявити, чи можна визнати, що штучний інтелект здатний мати майно та права інтелектуальної власності. Для досягнення цієї мети використовуються діалектичні, порівняльні, догматичні та юридичні методи. Зазначається, що згідно з останніми дослідженнями, є все більше підстав для визнання штучного інтелекту суб’єктом правовідносин. Особливу увагу в статті приділено особливостям стану штучного інтелекту у відносинах власності. Проаналізовано наслідки наділення штучного інтелекту правом власності. Зроблено висновок про доцільність такого підходу, оскільки це вирішить проблему відповідальності за шкоду, заподіяну штучним інтелектом. Запропоновано можливість наділення штучного інтелекту власністю на основі довіри до вирішення питання про його правосуб’єктність. У статті розглянуто сучасні підходи до проблеми прав на об’єкти творчості, створені штучним інтелектом. Варіанти розподілу прав на такі об'єкти аналізуються залежно від ступеня участі людини у їх створенні та від рівня складності штучного інтелекту, що створює ці об'єкти. Зроблено загальний висновок про можливість кваліфікувати штучний інтелект як суб'єкт правовідносин, зокрема відносин власності та інтелектуальної власності.

В статье анализируется возможность наделения искусственного интеллекта дееспособностью, что приведет к появлению нового субъекта правоотношений. Цель статьи - выяснить, можно ли признать, что искусственный интеллект может обладать правами собственности и интеллектуальной собственности. Для достижения этой цели используются диалектический, сравнительный, догматический и правовой методы. Отмечается, что согласно последним исследованиям, появляется все больше оснований для признания искусственного интеллекта субъектом правоотношений. Особое внимание в статье уделяется специфике статуса искусственного интеллекта в имущественных отношениях. Анализируются последствия наделения искусственного интеллекта правом собственности. Делается вывод о целесообразности такого подхода, поскольку это решит проблему ответственности за ущерб, причиненный искусственным интеллектом. Предлагается возможность наделения искусственного интеллекта правом собственности на доверительной основе до решения вопроса о его правосубъектности. В статье рассматриваются современные подходы к проблеме прав на объекты творчества, созданные искусственным интеллектом. Варианты распределения прав на такие объекты анализируются в зависимости от степени участия человека в их создании и от уровня сложности искусственного интеллекта, создающего эти объекты. Сделан общий вывод о возможности квалифицировать искусственный интеллект как субъект правоотношений, в частности отношений собственности и интеллектуальной собственности.
Nekit K. Artificial intelligence as a potential subject of property and intellectual property relations / K. Nekit, V. Tokareva, V. Zubar // Ius Humani Law Journal. - V. 9 (1). - Universidad de Los Hemisferios, 2020. - P. 231-250.